1961
DOI: 10.1063/1.1701225
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and Inelastic Scattering of Low-Velocity H+ and H2+ in Hydrogen

Abstract: Cross sections have been measured in the energy range 4 to 400 ev for elastic scattering and charge exchange of H+ and H2+ ions in hydrogen. The results are compared with similar measurements for deuterium ions in deuterium. Charge exchange was observed over the entire energy range for H2+, but was detected only above 50 ev for H+. Constants for empirical potential functions have been evaluated and are tabulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1963
1963
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Previous measurements of the CT total cross section have been performed by Cramer [15], McClure [16], Gealy and Van Zyl [17], and Kusakabe et al [18]. While the total cross sections obtained in all these experiments are practically identical for E > 500 eV, discrepancies at low energies are noticeable.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Previous measurements of the CT total cross section have been performed by Cramer [15], McClure [16], Gealy and Van Zyl [17], and Kusakabe et al [18]. While the total cross sections obtained in all these experiments are practically identical for E > 500 eV, discrepancies at low energies are noticeable.…”
mentioning
confidence: 82%
“…The CT process is thus described in the framework of the Franck-Condon approximation, where the target nuclei remain fixed during the collision. As the energy decreases below 1 keV, this [15]; (blue filled downward triangle) McClure [16]; (blue filled diamond) Gealy and Van Zyl [17]; (blue filled upward triangle) Kusakabe et al [18]. Recommended data: (red dash-dotted line) Phelps [19].…”
mentioning
confidence: 99%
“…Elizaga et al 15 also investigated electron capture in the same collisions using an eikonal treatment with the sudden approximation to describe target vibration and rotation. Although the sudden approximation is more accurate than the simple Franck-Condon (FC) approximation, it was found that it severely underestimates the capture cross section measured in the ion-beam-gas-cell 16,17 and crossed-beams experiments 18 for E < 200 eV. The origin of this failure was traced back 19 to the inability of the sudden approximation to represent the two-step quasiresonant mechanism, responsible for capture at low energies.…”
Section: Introductionmentioning
confidence: 98%
“…Figure 8, from S. K. Allison [8] and W. H. Cramer [9], shows measured values of the charge-exchange cross section <r cx for protons in hydrogen and its variation with energy. We use Ocx VH+/V 0 as the effective charge-exchange cross section and plot this quantity also in Fig.…”
Section: Evaluation Of Resultsmentioning
confidence: 99%